UJI EFEKTIFITAS Beauveria basianna dan Bacillus thuringiensis TERHADAP ULAT API (Setothosea asigna Eeck, Lepidoptera, Limacodidae) DI LABORATORIUM - Boy Tarigan Boy Tarigan; Syahrial Syahrial; Mena Uly Tarigan (Universitas Sumatera Utara, 2013)
ABSTRACTPalm oil tree is the most productif than the other nabaty oil plant. Setothosea is the primaryleaf eaten on palm oil tree. Test Effectiveness of Bacillus thuringiensis and Beauveriabasianna Caterpillars Against Fire Setothosea asigna Eecke in laboratory. The research wasconducted at the Laboratory of Plant Pests Faculty of Agriculture, University of NorthSumatra, Medan with altitude ± 32 meters above sea level. The research method used is nonCompletely Randomized Design factorial. The parameters in the observed percentagemortality of larvae of the caterpillar is Setothosea asigna fire. The results show thepercentage of mortality of silkworm larvae using Beauveria basianna flames were highest intreatment by 100% I3 is the observation of the IV, percentage mortality of silkworm larvaeusing Bacillus thuringiensis flames were highest in I6 treatment was 100% in the observationof the IV.Keywords : test effectiveness,Caterpillars Against Fire, Laboratory